Analisis Pengendalian Persediaan Bahan Baku sengan Metode Material Requirement Planning pada Batik Ragil di Masaran Sragen - Latifatul Azizah; Sunarso (Teewan Journal Solutions, 2025)
UMKM Batik Ragil is a business engaged in textiles, especially stamped batik, in its production process requires raw materials that must be maintained so that the production process can run smoothly. Raw material inventory is the main factor in efforts to support the smooth running of the production process, both in large and small companies. The key to a smooth production process is with optimal and sufficient raw material inventory control. A company needs inventory, without inventory the company will run the risk of not being able to meet consumer needs. The purpose of this study was to analyze the efficiency of raw material inventory control for mori cloth using the Material Requirement Planning (MRP) method, which consists of the Lot For Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ) methods. The results of the study showed that the total cost of raw material inventory according to the policy of the Batik Ragil business owner in Masaran was Rp 933.660 greater than the calculation using the MRP method. The total cost of raw material inventory with the Lot For Lot (LFL) method is Rp 336,000, EOQ is Rp 1.559.100 and with the POQ method is Rp 336,000. From the results of the calculation of the total cost of raw material inventory, the MRP method can make raw material inventory costs more efficient, especially the LFL and EOQ methods.